2010
DOI: 10.1111/j.1600-9657.2009.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for esthetic tissue preservation of a fresh extraction socket by an implant treatment concept simulating a tooth replantation

Abstract: In cases of an immediate insertion and loading of implants after a traumatic loss of the patient's own dentition or due to an inevitable extraction of an anterior tooth, it is essential to provide the patient with an adequate provisional crown. A soft-tissue recession must be avoided, whether it is due to a compression of the peri-implant soft-tissue caused by an over-dimensioned restoration in the cervical collar of the provisional crown or to a too small dimensioned sulcus former. A simulation of the exact d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…Cellular adhesion to customized healing abutments may support the peri‐implant mucosa and maintain its architecture . Moreover, based on the prosthetic socket seal concept, this device acts protecting and containing any bone substitute that fills the gap beneath it, avoiding a more invasive procedure to obtain primary wound closure . In addition, it has been suggested that a stabilization of the graft material either by placing a contoured healing abutment or a provisional restoration would limit contour changes of the ridge .…”
Section: Discussionmentioning
confidence: 99%
“…Cellular adhesion to customized healing abutments may support the peri‐implant mucosa and maintain its architecture . Moreover, based on the prosthetic socket seal concept, this device acts protecting and containing any bone substitute that fills the gap beneath it, avoiding a more invasive procedure to obtain primary wound closure . In addition, it has been suggested that a stabilization of the graft material either by placing a contoured healing abutment or a provisional restoration would limit contour changes of the ridge .…”
Section: Discussionmentioning
confidence: 99%
“…Occlusion was adjusted to avoid any functional loading. Definitive ceramic restorations were placed 3-4 months after the surgery [19]. Patients were enrolled in a yearly control program.…”
Section: Surgical and Prosthetic Protocolsmentioning
confidence: 99%
“…One year follow up showed stable soft tissue architecture with optimal esthetics (figure 13,14). (27) In conclusion, utilizing all the aforementioned techniques was shown to maintain the bone and soft tissue contour in the case presented. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 When clinicians face a situation regarding whether to extract a tooth or not, the decision is not easy to make.…”
Section: Prosthetic Treatmentmentioning
confidence: 72%